Occupancy tax within tax models of nautical tourism in the Mediterranean - Vukić, Luka (Array, 2018)
The existing tax models in nautical tourism, different for an individual country, contain various additional taxes already analyzed in scientific researches, while the characteristics and impacts of occupancy tax have been left neglected. The aim of the paper is to examine the impact of occupancy tax on the competitiveness of the price policy in nautical tourism within the Mediterranean countries, by performing the comparative analysis of tax models between the European Union member states and other Mediterranean countries. The results obtained have shown different and hardly comparable tax models, determined by the strategic orientation of the individual country in nautical tourism. The charges of the representatives of two target groups, the occupancy tax prices in Montenegro and similar models in Croatia and Greece have been compared, where the research findings indicated Montenegro as more competitive than the two other EU countries in all categories of the analysis. The obtained results have neglected other destinations comparative advantages mainly favorable to the EU countries having excellent development perspectives. The small scale participation of the occupancy tax in the overall tax model should not allow long-term outflow of the users in the European Union’s nautical tourism due to short-term revenue growth.